ESG, ESG rating divergence and earnings management: Evidence from China - Mao, Zhihong; Wang, Siyang; Lin, Yu‐En (Corporate social-responsibility and environmental management, 2024)
The existing studies on the relationship between ESG and earnings management provide mixed evidence and ignore ESG rating divergence. Using a sample of Chinese listed firms from 2009 to 2021, we examine the effect of ESG performance on earnings management under different levels of ESG rating divergence. The results reveal a negative association between ESG performance and earnings management. Meanwhile, among firms with high (low) ESG rating divergence, our results show that the degree of earnings management rises (falls) when the firms engage in ESG practices. Our findings are robust to alternative variable definitions and the Heckman two‐stage selection model. In addition, we exclude alternative explanations and consider the effect of greenwashing. Cross‐sectional analyses show that the moderating effect of ESG rating divergence is significant only among firms with greater CEO power and higher agency costs, suggesting that agency problems are the mechanism by which ESG rating divergence positively moderates the relationship between ESG performance and earnings management. This study advances the existing research on ESG and earnings quality by presenting new empirical evidence and revisits ESG rating divergence through the lens of agency theory, revealing that management could use ESG for opportunistic behavior in the presence of ESG rating divergence. Our study shows that the divergence in ESG ratings can affect the economic consequences of firms' ESG practices, offering insights for future research on ESG and ESG rating divergence and for regulators to improve the regulation of ESG disclosure and rating.